2019
DOI: 10.1080/2331205x.2019.1567973
|View full text |Cite
|
Sign up to set email alerts
|

A community-based diabetes group pilot incorporating a community health worker and photovoice methodology in an urban primary care practice

Abstract: Objective: The purpose of this study is to evaluate a three-month, community-based, diabetes self-management pilot intervention using photovoice, a community health worker (CHW), and group education sessions in an urban, African-American safety-net population, a group disproportionately affected by diabetes, in order to identify promising diabetes management approaches. Design: We invited patients with poorly-controlled diabetes from diabetes "hotspots" in Boston, located in African-American communities, to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The PRSIMA diagram describing study selection is shown in Figure 3 ( 47 ). In total the views and perceptions of 387 participants were described, with 15 studies conducted in the USA, one in Canada and another in Australia; of these seven focussed on Latino populations ( 48 54 ); five African American ( 55 59 ); one mixed of both populations ( 60 ), one Native American ( 61 ), one Punjabi ( 62 ); one Aboriginal ( 63 ); and one on Pacific Islanders ( 64 ). Papers were published between 2009 and 2022.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRSIMA diagram describing study selection is shown in Figure 3 ( 47 ). In total the views and perceptions of 387 participants were described, with 15 studies conducted in the USA, one in Canada and another in Australia; of these seven focussed on Latino populations ( 48 54 ); five African American ( 55 59 ); one mixed of both populations ( 60 ), one Native American ( 61 ), one Punjabi ( 62 ); one Aboriginal ( 63 ); and one on Pacific Islanders ( 64 ). Papers were published between 2009 and 2022.…”
Section: Resultsmentioning
confidence: 99%
“…Participants described their overall appreciation for the involvement of CHWPs in terms of their communication style and the way in which they made participants feel at ease ( 48 – 53 , 55 , 60 65 ). As one African American participant described:…”
Section: Resultsmentioning
confidence: 99%
“…Online Resource 4 gives an overview of the 28 included studies. There were eighth randomized controlled trials 11 , 12 , 22 , 26 , 29 , 35 , 42 , 44 but the majority pre-post evaluations ( n = 14) 23–25 , 27 , 28 , 30 , 31 , 34 , 38–40 , 43 , 45 , 46 and the remaining non-randomized intervention studies ( n = 3) 33 , 36 , 41 or presenting cross-sectional data ( n = 3). 21 , 32 , 37 Seventeen studies were reported in peer-reviewed academic journals, 11 , 12 , 22 , 24–26 , 28–34 , 37 , 43–45 six postgraduate theses 27 , 35 , 36 , 40–42 and five conference abstracts.…”
Section: Resultsmentioning
confidence: 99%
“…Online Resource 4 further shows that the large majority of studies were conducted in the USA ( n = 21). 11 , 12 , 22–28 , 30–32 , 34 , 35 , 37–39 , 41–43 , 46 Thirteen studies reported on PV with service users, 11 , 12 , 22 , 23 , 25 , 28 , 30 , 33 , 35 , 38 , 41 , 43 , 46 three with healthcarers. 26 , 34 , 45 Ethnic minority groups were represented in 13 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation